A Preliminary Study: Why Develop High Order Thinking Skills Worksheets Based on the 3N - Fitria Sulistyowati; Esti Harini (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
This qualitative research is a preliminary study of a 4-D model development research that aims to describe the basic problems, student characteristics, the formulation of learning outcomes, and specific learning goals as the initial stage of developing a high order thinking skills (HOTS) exercise bank based on 3N in Algebra. Research subjects at the analysis stage of student characteristics are all students taking Algebra courses in Mathematics Education Department Universitas Sarjanawiyata Tamansiswa for the 2019/2020 academic year. Data were collected using a literature study, observation, documentation. The data obtained were analyzed descriptively with the following steps: (1) preparing the data, (2) data coding, (3) searching for findings, (4) constructing the framework, and interpreting the data. The results of this study are: (1) Algebra learning centered on lecturers and students has difficulty solving non-routine problems, (2) there are only 1.59% of students who implemented to check the correctness of solutions in solving HOTS problems, (3) CPMK Algebra, and (4) formulation of specific learning goals. These results are used as a reference in the design stage of exercise bank development. Keywords: high order thinking, exercise bank, problem-solving.